Common Tripled Fixed point Theorems for ψ-Geraghty-Type Contraction Mappings Endowed with a Directed Graph: Tanadon Chaobankoh, Phakdi Charoensawan - Team, Support (Thai Journal of Mathematics, 2017)
The purpose of this paper is to present some existence and uniqueness results for tripled coincidence point and common tripled fixed point of ψ-Geraghtytype contraction mappings in complete metric spaces endowed with a directed graph. Some applications supported our main results are also given.